Superman the ultimate guide to the Man of Steel - Wallace, Daniel 1970-; Shuster, Joe 1914-1992; Siegel, Jerry 1914-1996; DC Comics, Inc (New York DK Pub, 2013)
"Readers can now get a comprehensive look at the complete Superman story from his birth on Krypton and arrival on Earth, to his double life as a Daily Planet reporter and as one of the most famous super heroes ever."--Amazon.com
"Superman created by Jerry Siegel and Joe Shuster."
Famous People
Includes index
1
Keywords: Superman -- (Fictitious character); Famous People